Coherent transfer between low-angular-momentum and circular Rydberg states - Signoles, Adrien; Dietsche, E. K.; Facon, A.; Grosso, D.; Haroche, S.; Raimond, J. M.; Brune, M.; Gleyzes, S. (Physical review letters, 2017)
We realize a coherent transfer between a laser-accessible low-angular-momentum Rydberg state and the circular Rydberg level with maximal angular momentum. It is induced by a radio frequency field with a high-purity σ+ polarization resonant on Stark transitions inside the hydrogenic Rydberg manifold. We observe over a few microseconds more than 20 coherent Rabi oscillations between the initial Rydberg state and the circular level. We characterize these many-Rydberg-level oscillations and find them in perfect agreement with a simple model. This coherent transfer opens the way to hybrid quantum gates bridging the gap between optical communication and quantum information manipulations with microwave cavity and circuit quantum electrodynamics.